Comprehensive expression analysis with cell-type-specific transcriptome in ALS-linked mutant SOD1 mice: Revisiting the active role of glial cells in disease - Yamashita, Hirofumi; Komine, Okiru; Fujimori-Tonou, Noriko; Yamanaka, Koji (Frontiers in Cellular Neuroscience, 2023)
Non-cell autonomous mechanisms are involved in the pathogenesis of amyotrophic lateral sclerosis (ALS), an adult neurodegenerative disease characterized by selective motor neuron loss. While the emerging role of glial cells in ALS has been noted, the detailed cell-type-specific role of glial cells has not been clarified. Here, we examined mRNA expression changes using microarrays of the spinal cords of three distinct lines of mutant SOD1 transgenic mice, an established ALS model. Our analysis used a transcriptome database of component cell types in the central nervous system (CNS), as well as SOD1G93A cell-type transcriptomes. More than half of differentially expressed genes (DEGs) were highly expressed in microglia, and enrichment analysis of DEGs revealed that immunological and degradation reactions were profoundly involved. Our analysis focused on DEGs that are highly expressed in each cell type, as well as chemokines, caspases, and heat shock proteins. Disease-associated microglial genes were upregulated, while homeostatic microglial genes were not, and galectin-3 (Mac2), a known activated microglial marker, was predicted to be ectopically expressed in astrocytes in mutant SOD1 mice. In mutant SOD1 mice, we developed a prediction model for the pathophysiology of different cell types related to TREM2, apolipoprotein E, and lipoproteins. Our analysis offers a viable resource to understand not only the molecular pathologies of each CNS constituent cell type, but also the cellular crosstalk between different cell types under both physiological and pathological conditions in model mice for various neurodegenerative diseases.